2023
DOI: 10.1038/s41388-023-02619-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the E3 ligase NEDD4 as a novel therapeutic strategy for IGF1 signal pathway-driven gastric cancer

Abstract: The IGF1 signal pathway is highly activated in some subtype of gastric cancer(GC) that exhibits poor survival and chemotherapy resistance. Although the results of clinical trials of anti-IGF1R monoclonal antibodies and IGF-1R inhibitors have been mostly disappointing in unselected cancer patients, some patients benefit from anti-IGF1R therapy in these failed studies. Therefore, it is necessary to characterize the complex IGF signaling in GC and help refine the strategies targeting the IGF1 pathway. We found th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…This in ammatory environment may contribute to changes in gastric mucosa, as chronic in ammation has been recognized as a precursor to cancer initiation and progression [21]. Both AIP and TyG are indicative of insulin resistance, a key component of MetS, while insulin resistance can lead to hyperinsulinemia and increased levels of insulin-like growth factors, which have been implicated in gastric carcinogenesis [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…This in ammatory environment may contribute to changes in gastric mucosa, as chronic in ammation has been recognized as a precursor to cancer initiation and progression [21]. Both AIP and TyG are indicative of insulin resistance, a key component of MetS, while insulin resistance can lead to hyperinsulinemia and increased levels of insulin-like growth factors, which have been implicated in gastric carcinogenesis [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows the list of inhibitors targeting ERK, PKC (protein kinase C), PKG (protein kinase G), CK1 (casein kinase 1), protein kinase PAK2, PAK4, and LKB1 (liver kinase B1) [ 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. Others enzyme inhibitors against protein phosphatase, such as (PPM1A/PP2CA, SCP), ubiquitin ligase (NEDD4-2/NEDD4L, HSC70-interacting protein, CHIP, SCFskp1 SCFskp2,) histone acetyltransferase (p300/CREB), and methyltransferase (SET 7/9, SETDB1/ESET, m6 methyltransferase, PRAP1), are listed in Table 2 [ 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , …”
Section: Regulation Of Smad Activity By Post-translational Modificati...mentioning
confidence: 99%
“…Ke Wang et al found that NEDD4 overexpression promoted tumor proliferation in insulin-like growth factor 1 receptor (IGF1R)-dependent GC cells, and therefore hypothesized that NEDD4 specifically promotes the growth of GC cells that are dependent on the IGF1/IGF1R signaling pathway by antagonizing the protein phosphatase activity of IRS 1 by antagonizing PTEN. Thus, NEDD4 may be one of the therapeutic targets for the treatment of GC driven by the IGF 1 signaling pathway [83,84]. Recently, Liang Xu et al reported that the expression of inhibin 2 (PHB 2) in GC tissues was significantly higher than in normal tissues adjacent to the cancer and was associated with poor clinical prognosis.…”
Section: Nedd4/nedd4l Inmentioning
confidence: 99%
“…This unveils a new target for the treatment of CRC [94] (p. 21). Recently, Ying-Nan Wang et al cultured CRC cells with cholesterol-lowering agents and lipoprotein-free medium, and found that SR10 [84], a RAR-related orphan receptor α/γ (RORα/γ) agonist, could activate the transcription of NEDD4 by binding to the promoter of the NEDD4 gene, thus promoting the ubiquitylation and degradation of c-myc and inhibiting the proliferation and metastasis of CRC cells. Moreover, atorvastatin combined with ROR α/γ agonists was found to have a synergistic effect in inhibiting the proliferation and migration of CRC cells, which provides a new strategy for CRC therapy by inhibiting the cholesterol-ROR α/γ-c-myc axis [91].…”
Section: Nedd4/nedd4l and Colorectal Cancermentioning
confidence: 99%